Uso de conservadores naturais na elaboração de carne de sol com teores reduzidos de cloreto de sódio - Campêlo, Maria Carla da Silva (Universidade Federal Rural do Semi-Árido, 2016)
Meat and meat products undergo deterioration processes very easily, for this reason, we often use conservational methods to increase shelf life and add value to these products. Among these, salting is a very common technique, used for a very long time, to expand shelf life. However, ingesting great amounts of sodium chloride may lead to the development of arterial hypertension and secondary cardiovascular diseases. Hence, we aimed to evaluate the quality of carne de sol produced with lower levels of sodium chloride and the addition of natural conservative agents. For such purpose, we obtained beef in natura, which was then cut and divided into the following four sample groups: CLS – carne de sol with sodium lactate; CAL – carne de sol with lactic acid; CAL+LS – carne de sol with lactic acid and sodium lactate; and Control – carne de sol with no treatment. Afterwards, the meat underwent the salting process with the sodium chloride level at 2% and was stored at refrigeration temperature 4°C ±1°C. Microbiological and physicochemical analyses were performed on the in natura beef, to evaluate the quality of the raw material that was used, and on the carne de sol produced with each treatment, which were analyzed on day 0, immediately after the addition of the conservative agents, and on days 3, 6, 9 and 12 of refrigerated storage. The carne de sol containing natural conservative agents presented lower microbiological counts when compared to the Control group, and group CAL should be highlighted, because it demonstrated increase in shelf life of up to six days of storage. Regarding the physicochemical parameters, the conservative agents did not significantly change the quality of the samples. Therefore, lactic acid and sodium lactate can be considered as feasible alternatives to prolong the shelf life of carne de sol, and reduce the levels of sodium chloride that are used
Use of natural conservative agents production of carne de sol with lower levels of sodium chloride
Keywords: Qualidade; Físico-química; Microbiológica; Ácido lático; Lactato de sódio; Quality physicochemical; Lactic acid,; Sodium lactate; CIENCIAS AGRARIAS::MEDICINA VETERINARIA